One-step radiosynthesis and initial evaluation of a small molecule PET tracer for PD-L1 imaging. Issue 24 (15th December 2020) - Miao, Yinxing; Lv, Gaochao; Chen, Yinfei; Qiu, Ling; Xie, Minhao; Lin, Jianguo
Graphical abstract: Highlights: [ 18 F]LN as a small molecule PD-L1 tracer was synthesized for PET imaging. The radiotracer [ 18 F]LN was fluoridated via 18 F- 19 F isotope exchange. [ 18 F]LN targeted tumor site of PD-L1 transfected melanoma-bearing mice. Abstract: Programmed cell death protein-ligand 1 (PD-L1) is a crucial biomarker in immunotherapy and its expression level plays a key role in the guidance of anti-PD-L1 therapy. It had been reported that PD-L1 was quantified by noninvasive imaging with more developed radiotracers. In our study, a novel [ 18 F]fluoride labeled small molecule inhibitor, [ 18 F]LN was designed for positron emission tomography (PET) imaging in both PD-L1 transfected (A375-hPD-L1) and non-transfected (A375) melanoma-bearing mice. LN showed the specificity (IC50 = 50.39 ± 2.65 nM) to PD-L1 confirmed by competitive combination and cell flow cytometry (FACS) analysis. The radiotracer [ 18 F]LN was obtained via 18 F- 19 F isotope exchange from precursor LN . After radiosynthesis, [ 18 F]LN was achieved with a high radiochemical purity (RCP) above 95% and got a favorable molar activity of 36.34 ± 5.73 GBq/μmol. [ 18 F]LN displayed the moderate affinity (Kd = 65.27 ± 3.47 nM) to PD-L1 by specific binding assay. And it showed 1.3-fold higher uptake in A375-hPD-L1 cells than that in A375 cells. PET imaging revealed that [ 18 F]LN could enter into PD-L1 expressing tumor site and visualize the outline of tumor. And tumor uptake (1.96 ± 0.27 %ID/g) reached the maximum at 15 min in the positive group, showed 2.2-fold higher than the negative (0.89 ± 0.31 %ID/g) or the blocked (1.07 ± 0.26 %ID/g) groups. Meanwhile, biodistribution could slightly distinguish the positive from the negative. The results indicated [ 18 F]LN would become an efficient tool for evaluating PD-L1 expression with further optimization.